The Growing Burden of Disability Related to Nonalcoholic Fatty Liver Disease: Data From the Global Burden of Disease 2007‐2017 - Paik, James M. (Hepatol Commun, 2020)
Chronic liver disease (CLD) is a growing cause of morbidity and mortality worldwide. The burden of CLD varies according to etiology and geographic location. We assessed the global burden of disability from the most important complications of CLD (cirrhosis and liver cancer [LC]) according to the most common etiologies between 2007 and 2017. We obtained years living with disability (YLD), years of life lost (YLL), and disability‐adjusted life‐years (DALYs) data from the Global Burden of Disease 2017 study. Between 2007 and 2017, LC DALYs decreased by 4.52% and cirrhosis DALYs decreased by 10.58%. Nevertheless, in 2017, CLD caused 62.16 million DALYs (33.4% LC and 66.5% cirrhosis), of which 96.8% came from YLL (34.1% LC and 65.9% cirrhosis) and 3.2% from YLD (11.6% LC and 88.4% cirrhosis). In 2017, Asia accounted for 66% of all DALYs globally. Central Asia, Africa regions, Southeast Asia, and Eastern Europe had the highest liver‐related DALYs (≥1,000 per 100,000), whereas the lowest rates (≤500 per 100,000) were seen in high‐income regions, such as Asia Pacific, North America, Western Europe, and Australasia. In 2007, hepatitis B virus caused the majority (47.5%) of liver‐related DALYs, followed by hepatitis C virus (23.7%), alcoholic liver disease (14.2%), and nonalcoholic fatty liver disease/nonalcoholic steatohepatitis (NAFLD/NASH) (6.4%). In 2017, these rates shifted to 45.7%, 24.1%, 4.8%, and 7.1%, respectively. Between 2007 and 2017, cirrhosis‐related DALYs due to NAFLD/NASH increased by 23.4%, whereas the increment was 37.5% for LC‐related DALYs due to NAFLD/NASH. Conclusion: DALYs due to viral hepatitis still account for the largest proportion of CLD‐related DALYs. Although DALYs from all other liver diseases have remained stable in the last decade, DALYs related to NAFLD/NASH are growing. National, regional, and global policies are needed to address the disability burden of NAFLD across the world.